POLYMORPHISM AND INTERSPECIFIC VARIABILITY OF CYTOCHROME OXYDASE SUBUNIT I (COI) GENE NUCLEOTIDE SEQUENCE IN SIBLING SPECIES of A AND B Anopheles messeae AND An. beklemishevi (DIPTERA: CULICIDAE) - O. V. Vaulin; Yu. M. Novikov (Вавиловский журнал генетики и селекции)
Species identification of159 individuals of the Anopheles maculipennis complex from 5 localities ofUral andSiberia was conductedbyPCR-RFLP ITS2. The DNA sequences ofa COI gene fragment were determinedin 124 individuals from the localities. The Anopheles messeae groupCOI sequences were comparedwiththose from a DNA database. VariabilityofCOI nucleotide sequences (measures H andπ) ofthe crypticspecies A andB Anopheles messeae andAn. beklemishevi was investigatedandquantitativelyestimated. It was foundthat the COI variabilitydidnot allow discrimination ofthe crypticspecies A andB Anopheles messeae. Neither didit show anygeographicregularityfor these species. It is concludedthat the COI polymorphism ofthe A andB Anopheles messeae species is common for them, as well as the chromosomal inversion polymorphism. It arose long before their divergence. The diagnosticimportance ofinterspecificITS2 variabilityis confirmed.